Situation Report: Czechoslovakia, 11 November 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Indra Speech on Russian Revolution Anniversary The Czechoslovak Countryside Criticism of Light Literature Czech Music under the Shadow of Politics Pavol Licko Imprisoned